Nitric Oxide Releasing Nanoparticles for Treatment of Candida Albicans Burn Infections - Macherla, Chitralekha; Sanchez, David A.; Ahmadi, Mohammed; Vellozzi, Ernestine M.; Friedman, Adam J.; Nosanchuk, Joshua D.; Martinez, Luis R. (Frontiers in Microbiology, 2012)
Candida albicans is a leading fungal cause of burn infections in hospital settings, and sepsis is one of the principle causes of death after a severe burn. The prevalence of invasive candidiasis in burn cases varies widely, but it accounts for 3-23% of severe infection with a mortality rate ranging from 14% to 70%. Therefore, it is imperative that we develop innovative therapeutics to which this fungus is unlikely to evolve resistance, thus curtailing the associated morbidity and mortality and ultimately improving our capacity to treat these infections. An inexpensive and stable nitric oxide (NO)-releasing nanoparticle (NO-np) platform has been recently developed. NO is known to have direct antifungal activity, modulates host immune responses and is a significant regulator of wound healing. In this study, we hypothesized that NO-np would be an effective therapy in the treatment of C. albicans burn infections. Using a murine burn model, NO-np demonstrated antifungal activity against C. albicans in vivo, most likely by arresting its growth and morphogenesis as was demonstrated in vitro. Moreover, we showed that NO-np significantly accelerated the rate of wound healing in cutaneous burn infections when compared to controls. The histological evaluation of the affected tissue revealed that NO-np treatment modified leukocyte infiltration, minimized the fungal burden, and reduced collagen degradation, thus providing potential mechanisms for the therapeutics’ biological activity. Together, these data suggest that NO-np have the potential to serve as a novel topical antifungal which can be used for the treatment of cutaneous burn infections and wounds.